Pengaruh Motivator Insentif pada Kinerja Karyawan dengan Kepercayaan Diri sebagai Pemediasi (Universitas Negeri Semarang, 2015)
The purpose of this research is to examine the influence of incentive’s motivator on the employee’s performance with self esteem as mediation (the case study on the employees of PT. Prima Cahaya Indobeverage in Ungaran). The populations in this research are all the employees of PT. Cahaya Indobeverage in Ungaran. The number of samples used in this research as much as 72 employees, using the Purposive Sampling method. The methods of collecting data are using interviews and questionnaires. The result of data analysis is using SPSS program version 17 shows that there are a positive influence and significant incentive’s motivator, and self esteem against the employee’s performance. And there is a direct positive influence and significant incentive’s motivator to self esteem. Also with the variable of self esteem directly affect in positive and significant which mediated incentive’s motivator against the employee’s performance of PT. Prima Cahaya Indobeverage in the Ungaran.